Cotas para a distância mínima de códigos de Goppa envolvendo o piso e o teto de um divisor - Tognon, Carlos Henrique (2011)
In this work we study the basics of function eld theory and coding theory, including geometric Goppa codes, derivations, dierential forms and also results on the ceiling and oor of divisors. We present two bounds for the minimum distance of a geometric Goppa code, both involving the oor of a divisor and yielding good estimates for the true value of the minimum distance. We also present a bound related to the ceiling of a divisor; the work ends with examples dealing with codes over the Hermitian and the Suzuki function elds.